KAJIAN TERHADAP KEMAMPUAN ASAM ORGANIK DAN ANORGANIK DALAM MELARUTKAN FOSFAT DARI BATUAN FOSFAT ALAM - Sudadi Sudadi (Faculty of Agriculture, Universitas Sebelas Maret, 2008)
Study of Organic and Inorganic Acid Capabilities in Solubilize Phosphatic Rock‐P. Phosphatic rock has been used as phosphate fertilizer for along time and now being an alternative of P fertilizer. But its low solubility making them uneffective source of P for plant. Many attempt to increases their solubility has been done i.e. by acidulated it with organic and inorganic acid. Inorganic acid solubilize mineral P by acidification while organic acid by acidification and maybe chelating mechanism. The aim of this research is to study the effectivity of the two kind of acid, organic (citric acid) and inorganic acid (sulphuric acid) in solubilizing phosphatic rock‐P. Research has conducted in May – Oct 2007 at Soil Biology Laboratory, Gadjah Mada University, Yogyakarta. The experiment arranged in Completely Randomized Design with three level of sulphuric acid concentration (0.00 M, 0.02 M and 0.04 M), three level of citric acid concentration (0.00 M, 0.02 M and 0.04M) and three kind of phosphatic rock (Christmas Island, Ciamis and Madura) origin. Each of combination treatment replicated three times. A gram of each phosphatic rock was added to 50 ml of aquades in 150 ml erlenmeyer flask and shoke continuously at 200 rpm in reciprocal shaker. Water soluble‐P and pH were analysed at 0, 3, 6 and 9 day after incubation time. All data was analysed for anova at 95% level of significance and continued with DMRT if any significance differences. Research show that inorganic acid (sulphuric acid) solubilize phosphatic rock‐P stronger than organic acid, except for high content Al phosphatic rock, where the two kind of acid have equal P‐solubilizing capacity. Maybe, the high P‐solubilizing capacity of organic acid for high Al‐phosphatic rock caused by its ability in chelating Al. Keywords: Fosfat, batuan fosfat alam, asam sitrat, asam sulfat